2006
DOI: 10.1007/s11205-005-5921-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of College Life (QCL) of Students: Developing and Validating a Measure of Well-Being

Abstract: college student quality of life, college student well-being, quality of college life of students, university student quality of life, university student well-being,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
0
16

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 19 publications
2
108
0
16
Order By: Relevance
“…Goodboy and Myers (2008) found that a variety of student factors are associated with student satisfaction as a learning outcome. Common measures of satisfaction among students Psychosocial Factors 5 assess positive emotions in the student's life as a whole, including personal satisfaction and satisfaction with university life (e.g., the College Descriptive Index, Reed, Lahey, & Downey, 1984; the Quality of College Life, Sirgy, Grezeskowiak, & Rahtz, 2007). The current study focused on students' satisfaction in a global sense, considering their levels of satisfaction with life as a whole during their time spent at college.…”
Section: Measuring College Student Successmentioning
confidence: 99%
“…Goodboy and Myers (2008) found that a variety of student factors are associated with student satisfaction as a learning outcome. Common measures of satisfaction among students Psychosocial Factors 5 assess positive emotions in the student's life as a whole, including personal satisfaction and satisfaction with university life (e.g., the College Descriptive Index, Reed, Lahey, & Downey, 1984; the Quality of College Life, Sirgy, Grezeskowiak, & Rahtz, 2007). The current study focused on students' satisfaction in a global sense, considering their levels of satisfaction with life as a whole during their time spent at college.…”
Section: Measuring College Student Successmentioning
confidence: 99%
“…The review has covered various domains including social inclusion and exclusion (Levitas et al, 2007;Scutella et al, 2010), student satisfaction (e.g. Price et al, 2003;Jiewanto et al, 2012); student engagement (Astin, 1984;Tinto 1993, Pascarella & Terenzini, 2005; quality of college life (Sirgy et al, 2007) and campus design and planning (Strange & Banning, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Joseph and Joseph, 1997;Price et al, 2003;Douglas et al, 2006;Petruzzellis et al, 2006;Gruber et al, 2010). The second approach indicates previous studies, which address student quality of life in universities (Sirgy et al, 2007;Arsalan & Akkas, 2013). The third approach is the one that measure student engagement by the National Survey of Student Engagement (NSSE).…”
Section: Introductionmentioning
confidence: 99%
“…Studies concerning college students and quality of life can be divided into three categories such as studies investigating associations between students' quality of life and potential factors; studies developing students' measures of quality of life and studies developing measures of students' college life (Sirgy et al, 2007). In this section, the present study deals with past research that determines factors affecting students' quality of life.…”
Section: Review Of Related Literaturementioning
confidence: 99%